Hepatitis B and C virus reactivations under biologic treatments in patients with rheumatic diseases: long-term results from a single-center - Coskun, Belkis Nihan; Yağız, Burcu; Özboz, Ezgi Sezen; Tufan, Ayşe Nur; Ermurat, Selime; Pehlivan, Yavuz; Dalkılıç, Hüseyin Ediz (The European Research Journal, 2022)
Objectives: To find out the effects and prevalence of disease-modifying antirheumatic drugs (DMARDs) and anti-TNF agents on hepatitis B virus (HBV) reactivation in hepatitis B surface antigen (HBsAg)-positive patients with rheumatic diseases (RD). Methods: This retrospective study was conducted on 1,548 RD patients. Patients’ medical records regarding immunological profiles, clinical courses, and outcomes, were obtained. In this research, the patient used conventional DMARDs (cDMARDs) and biological DMARDs (bDMARDs). A drug exposure was considered when a patient was administered GC, cDMARDs, or bDMARDs for > 4 weeks. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and bilirubin were measured. HBsAg, HBV DNA assay, anti-HCV and HIV were identified. Results: HBsAg was positive in 19 (37.3%) patients. Anti-HBs in 5 (9.8%) patients and anti-HBc IgG in 35 (68.6%) patients were positive. All patients with HBsAg positivity were receiving antiviral prophylaxis. Anti-HCV was positive in 25.5% (n = 13) of individuals . There was not any reactivation among the patients. No HBV reactivation was observed. Conclusions: Screening before treatment and give prophylaxis to patients who have occult hepatitis or hepatitis B, may be an important factor in the absence of reactivation. Hepatitis screening should be performed in all patients prior to biological treatment is initiated.